Rohr and Benz, Queenship and the Women of Westeros. Female Agency and Advice in Game of Thrones and A Song of Ice and Fire (Palgrave MacMillan, 2020) - Gabrielle Storey (Royal Studies Journal, 2022)
Review of Zita Eva Rohr and Liza Benz, Queenship and the Women of Westeros. Female Agency and Advice in Game of Thrones and A Song of Ice and Fire (Cham: Palgrave MacMillan, 2020).